Kegiatan Skrining Tekanan Darah Dan Penyakit Hipertensi Pada Populasi Dewasa Di Sekolah SMP Kalam Kudus - Alfred Sutrisno Sim; Fernando Nathaniel; Farell Christian Gunaidi; Tamia Asri Jeser; Laurensius Laurensius; Priscilla Elnatan Christina (SAFARI :Jurnal Pengabdian Masyarakat Indonesia, 2024)
Hypertension is a global public health problem that contributes to the leading cause of death and death worldwide. The prevalence of hypertension in Indonesia based on the results of blood pressure measurements in residents aged ≥18 years is 34.11%. Hypertension can be caused by 2 factors, namely risk factors that can be modified (diet, physical activity, alcohol, cigarettes) and risk factors that cannot be modified (age, gender, and genetics). Hypertension that is not managed properly can increase the risk of cardiovascular disease, cerebrovascular disease and chronic kidney disease. This activity uses sustainable methods in the form of PDCA (Plan-Do-Check-Action) and blood pressure measurement. It was found that 26 participants suffered from hypertension. Screening for hypertension is very important to prevent complications and produce a better quality of life.